Industry analysis and strategies for LED lighting industry in Malaysia - Lim, Vincent Hong Shen (2016)
As the global warming issue is getting serious, much attention have been given on environmental friendly products. With that, the latest technology lighting, LED lighting has act as an important in saving the earth as it emits lower carbon dioxide compared to the conventional lighting. Many researchers found that the particular LED lighting industry has a huge potential in the next decade due to its efficiency in the luminaire sector. This study aimed to analyze and recommend strategies for LED lighting industry in Malaysia. Basically, the dissertations is structured in five main chapters as below and believe to provide an insight towards the industry: (1) Introduction, referring to aim, scope (2) Literature Review, addressing the academic background for analyzing the industry (3) Methodology, describe the method used and the sample chosen for the study (4) Analysis of the research findings, analyse the research findings and recommend strategies for the current research (5) Conclusion, describe about the implication, research limitation and recommendations for future studies. The current study analyze the attractiveness of the LED lighting industries and also identify the strategies for the local firms with the help of Porter’s five forces framework and Porter’s generic strategies. This is because both theories was found to be the most capable theory for the current study. The research conducted in the form of semi-structured interviews with executives of the Malaysian LED lighting firms in the process of analyzing and recommend strategies for the industry as these executives are the one who know the industry the most. The findings found that the LED lighting industry is attractive as it has a huge potential of growth in the world as well as in Malaysia. In fact, all the five forces shown that the LED lighting industry in Malaysia is relatively attractive. However, it found that bargaining power of supplier and buyer affect the industry the most. Also, the study found that there are various key problem that the industry facing at the moment, such as the people in Malaysia are lack of knowledge towards the LED lighting products, insufficient of talent worker in the industry, and so on. Indeed, all of these problems and challenges can be solve when the firm position themselves correctly. The overall of the discussion found that differentiation would be the best for the local firms to sustain and compete in the industry. Apart from that, findings found that government act as an important for the sustainability of the firm in the industry. As a recommendation for future research, it is suggested that more sample selection of the industry and also more time horizon is require in order to obtain a more accurate and precise data.